Positive pole piece, preparation method thereof and lithium ion battery comprising positive pole piece

By adding lithium carbonate and organic acid to the slurry of the positive electrode material of the lithium-ion battery to form a microporous structure and lithium ion channel, the problems of material agglomeration and slurry settlement after nano- or micronization treatment are solved, and the conductivity and rate performance of the battery are improved.

CN119601663APending Publication Date: 2025-03-11MURATA MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311161743.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

After nano or micronization treatment, existing lithium-ion battery positive electrode materials are prone to particle agglomeration, slurry settlement and current collector fallout, which affects the cycle life and rate performance of the battery.

Method used

By adding lithium carbonate and organic acid to the slurry, the CO2 and H2O generated in the reaction are neutralized to form a microporous structure and more lithium ion channels, reducing the curvature and McMarin number of the electrode sheets, and improving the conductivity and rate performance.

Benefits of technology

Under the same body density, the curvature and McMarin number of the pole sheet are reduced, the conductivity and rate performance of the battery are improved, and the cycle life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601663A_ABST
    Figure CN119601663A_ABST
Patent Text Reader

Abstract

The invention discloses a positive pole piece, a preparation method thereof and a lithium ion battery comprising the positive pole piece. The positive pole piece comprises a positive active material, a positive conductive agent, a positive binder and organic acid lithium, and based on the total weight of the positive active material, the positive conductive agent, the positive binder and the organic acid lithium, the content of the organic acid lithium is 0.14-11.99 wt%. By adding lithium carbonate and organic acid into the slurry or soaking the pole piece in the organic acid and neutralizing CO2 and H2O generated in the reaction, a microporous structure and more direct lithium ion channels are generated in the pole piece in the drying process, so that the curved path rate and the Mecanum number of the pole piece are reduced under the same volume density, and the service life of the pole piece is prolonged. And the electrical properties such as conductivity and rate capability of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion battery electrode materials, and in particular to a positive electrode sheet, a preparation method thereof and a lithium ion battery comprising the same. Background Art

[0002] In order to improve the high-current charge and discharge performance of lithium-ion batteries to meet the high-power requirements of hybrid electric vehicles, one approach is to nanometer and micronize the positive and negative electrode materials. On the one hand, it can shorten the distance that lithium ions migrate in the electrode material particles, and on the other hand, it can increase the specific surface area of ​​the electrode material, making the embedding and de-embedding of lithium ions in the electrode material multi-pathway, thereby improving the high-current charge and discharge capacity of the electrode.

[0003] However, a new problem arises after the electrode material is nanosized or micronized. Since nano- and micron-sized materials have small particle sizes and high specific surface energy, they are easy to agglomerate and difficult to disperse. As a result, particles and slurry sedimentation are easy to occur on the electrode surface during the electrode preparation process, and the electrode material is easy to fall off from the current collector, which seriously affects the cycle life of the battery.

[0004] A method for dispersing micron-nano electrode materials is proposed in the prior art. By adding an organic acid that decomposes at 150°C to the slurry, the micron-nano material can be dispersed more evenly and stably. The method can prevent the slurry from settling, and the carbon dioxide and water decomposed by the organic acid at 150°C volatilize, thereby improving the capacity, initial efficiency and cycle life of the battery; at the same time, the adhesion between the electrode and the current collector after coating can be improved, thereby improving the cycle life of the battery.

[0005] However, these methods in the prior art do not study the neutralization effect of organic acids on residual alkali in electrode materials, the effect on pore formation in thick-coated electrodes and the inter-particle structure, and therefore do not involve research on reducing the tortuosity of the electrode and thus improving the rate performance of the material.

[0006] Moreover, although thick coating of electrode materials can increase the energy density of the battery, it has poor conductivity and rate performance. Summary of the invention

[0007] The main purpose of the present invention is to provide a positive electrode plate, a preparation method thereof and a lithium ion battery comprising the same, so as to solve the problems of poor processing performance, conductivity and rate performance in the prior art.

[0008] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a positive electrode plate is provided, comprising a positive electrode active material, a positive electrode conductor, a positive electrode binder and an organic acid lithium, wherein the content of the organic acid lithium is 0.14wt%-11.99wt% based on the total weight of the positive electrode active material, the positive electrode conductor, the positive electrode binder and the organic acid lithium.

[0009] Furthermore, in the above-mentioned positive electrode plate, the positive electrode plate contains micropores of 1-10 microns, and organic acid lithium is enriched around the micropores.

[0010] Furthermore, in the above-mentioned positive electrode sheet, the organic acid lithium is distributed on the surface of the positive electrode active material and the positive electrode conductive agent.

[0011] Furthermore, in the above-mentioned positive electrode plate, the organic acid radical in the organic acid lithium is derived from one or more of maleic acid, glycolic acid, acrylic acid, fumaric acid, malonic acid, succinic acid, malic acid, trisaccharic acid and aconitic acid.

[0012] Furthermore, in the above-mentioned positive electrode sheet, the positive electrode active material is selected from one or more of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, lithium titanate and lithium manganese iron phosphate.

[0013] Furthermore, in the above-mentioned positive electrode plate, the organic acid lithium is lithium maleate, and the content of lithium maleate is 0.23wt%-8.83wt%.

[0014] According to another aspect of the present invention, a method for preparing a positive electrode sheet is provided, comprising the following steps: - Step S1: mixing a positive electrode active material, a positive electrode conductor, a positive electrode binder and lithium carbonate to obtain a first slurry; - Step S2: adding an organic acid to the first slurry and mixing to obtain a second slurry, and then making the second slurry into a positive electrode sheet, or making the first slurry into a primary sheet, and then applying an organic acid to the primary sheet to make a positive electrode sheet.

[0015] Furthermore, in the above method, the method further comprises step S3: drying the positive electrode sheet obtained in step S2 to prepare a positive electrode sheet with micropores. Preferably, the drying temperature in step S3 is 100-150°C.

[0016] Furthermore, in the above method, the addition ratio of lithium carbonate is 0.05wt%-5wt% of the solid components in the first slurry.

[0017] Furthermore, in the above method, the organic acid is selected from one or more of maleic acid, glycolic acid, acrylic acid, fumaric acid, malonic acid, succinic acid, malic acid, trisaccharic acid and aconitic acid.

[0018] Furthermore, in the above method, the positive electrode active material is selected from one or more of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, lithium titanate and lithium manganese iron phosphate.

[0019] Furthermore, in the above method, the particle size of lithium carbonate is 50nm-10μm.

[0020] Furthermore, in the above method, step S1 includes the following steps: -Step S11: mixing the positive electrode conductor, the positive electrode binder and the solvent to obtain a uniform solution; -Step S12: adding lithium carbonate to the uniform solution to obtain a conductive glue solution; -Step S13: adding the positive electrode active material to the conductive glue solution to obtain a first slurry.

[0021] Furthermore, in the above method, step S2 includes the following steps: - step S21: adding an organic acid to the first slurry and mixing to obtain a second slurry, and then evenly coating the second slurry on an aluminum foil to form a positive electrode sheet; or - step S22: evenly coating the first slurry on an aluminum foil to form a primary electrode sheet, and then spraying an organic acid ethanol solution on the primary electrode sheet or soaking the primary electrode sheet with an organic acid ethanol solution to form a positive electrode sheet.

[0022] Furthermore, in the above method, after step S22, step S2 also includes step S23: cleaning the positive electrode plate with an ethanol solution.

[0023] According to another aspect of the present invention, a lithium-ion battery is provided, comprising: a positive electrode plate, a negative electrode plate and a separator, wherein the positive electrode plate is the positive electrode plate described above in the present invention or is prepared by the method described above in the present invention.

[0024] In the positive electrode plate, the preparation method thereof and the lithium ion battery containing the same of the present invention, by adding lithium carbonate to the slurry and adding organic acid to the slurry or soaking the plate in organic acid, CO2 and H2O generated in the neutralization reaction are generated in the plate during the drying process, so that the tortuosity and McMullin number (Nm) of the plate are reduced at the same body density, and the electrical properties of the battery such as conductivity and rate performance are improved. At the same time, the addition of organic acid can effectively reduce the residual alkali content in the positive electrode active material and improve the processing performance of the slurry. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of a positive electrode sheet made with or without the addition of lithium carbonate and organic acid additives.

[0026] Figure 2 It is a schematic diagram showing that CO2 and H2O generated by the reaction of lithium carbonate and organic acid produce a microporous structure in the electrode and that organic acid lithium is enriched near the micropores.

[0027] Figure 3 This is a fitting curve obtained according to the fitting method in the reference [Journal of The Electrochemical Society, 163(7)A1373-A1387(2016)]. DETAILED DESCRIPTION

[0028] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0029] As described in the background technology, only methods of dispersing micron-nano materials by organic acids have been proposed in the prior art. However, although these methods in the prior art can increase the energy density of the battery, they have poor conductivity and rate performance, and these methods do not study the neutralization effect of organic acids on the residual alkali of electrode materials. Therefore, further improvement is still needed. In response to the problems in the prior art, according to a typical embodiment of the present invention, a positive electrode plate is provided, comprising a positive electrode active material, a positive electrode conductive agent, a positive electrode binder and an organic acid lithium, wherein the content of the organic acid lithium is 0.14wt%-11.99wt% based on the total weight of the positive electrode active material, the positive electrode conductive agent, the positive electrode binder and the organic acid lithium.

[0030] Preferably, the positive electrode plate contains micropores of 1-10 microns, and organic acid lithium is enriched around the micropores.

[0031] Preferably, the organic acid lithium is distributed on the surface of the positive electrode active material and the positive electrode conductive agent.

[0032] In the technical solution of the present invention, by adding lithium carbonate to the slurry and adding organic acid to the slurry or soaking the pole piece in organic acid, CO2 and H2O generated in the neutralization reaction are generated in the positive pole piece during the drying process, so that the tortuosity and McMullin number of the pole piece are reduced at the same body density, and the electrical properties of the battery such as conductivity and rate performance are improved. At the same time, the addition of organic acid can effectively reduce the residual alkali content in the positive active material and improve the processing performance of the slurry.

[0033] Preferably, the content of organic acid lithium can be 0.14wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2.0wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3.0wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4.0wt%, 4.2wt%, 4.5wt%, 4.8wt%, 5.0wt%, 5.2wt%, 5.5wt%, 5.8wt%, 6.0wt%, 6.2wt%, 6.5wt%, 6.8wt%, 7. .0wt%, 6.2wt%, 6.5wt%, 6.8wt%, 7.0wt%, 7.2wt%, 7.5wt%, 7.8wt%, 8.0wt%, 8.2wt%, 8.5wt%, 8.8wt%, 9.0wt%, 9.2wt%, 9.5wt%, 9.8wt%, 10.0wt%, 10.2wt%, 10.5wt%, 10.8wt%, 11.0wt%, 11.2wt%, 11.5wt%, 11.8wt% or 11.99wt%.

[0034] Preferably, the size of the micropores inside the positive electrode sheet can be 1 micron, 1.1 micron, 1.2 micron, 1.3 micron, 1.4 micron, 1.5 micron, 1.6 micron, 1.7 micron, 1.8 micron, 1.9 micron, 2 micron, 2.1 micron, 2.2 micron, 2.3 micron, 2.4 micron, 2.5 micron, 2.6 micron, 2.7 micron, 2.8 micron, 2.9 micron, 3 micron, 3.1 micron, 3.2 micron, 3.3 micron, 3.4 micron, 3.5 micron, 3.6 micron, 3.7 micron, 3.8 micron, 3.9 micron, 4 micron, 4.1 micron, 4.2 micron, 4.3 micron, 4.4 micron, 4.5 micron, 4.6 micron, 4.7 micron, 4.8 micron, 4.9 micron, 5 micron, 5.1 micron, 5.2 micron, 5.3 micron, 5.4 microns, 5.5 microns, 5.6 microns, 5.7 microns, 5.8 microns, 5.9 microns, 6 microns, 6.1 microns, 6.2 microns, 6.3 microns, 6.4 microns, 6.5 microns, 6.6 microns, 6.7 microns, 6.8 microns, 6.9 microns, 7 microns, 7.1 microns, 7.2 microns, 7.3 microns, 7.4 microns, 7.5 microns, 7.6 microns, 7.7 microns, 7.8 microns, 7.9 microns, 8 microns, 8.1 microns, 8.2 microns, 8.3 microns, 8.4 microns, 8.5 microns, 8.6 microns, 8.7 microns, 8.8 microns, 8.9 microns, 9 microns, 9.1 microns, 9.2 microns, 9.3 microns, 9.4 microns, 9.5 microns, 9.6 microns, 9.7 microns, 9.8 microns, 9.9 microns or 10 microns.

[0035] In a further embodiment of the present invention, the organic acid radical in the organic acid lithium is derived from one or more of maleic acid, glycolic acid, acrylic acid, fumaric acid, malonic acid, succinic acid, malic acid, trisproitic acid and aconitic acid. The organic acids derived from the above list are easily commercially available and more economical, and by using the organic acids derived from the above list, CO2 and H2O can be better produced in the neutralization reaction, thereby generating more microporous structures and more direct lithium ion channels in the positive electrode sheet during the drying process.

[0036] In a further embodiment of the present invention, the positive electrode active material is selected from one or more of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, lithium titanate and lithium manganese iron phosphate. The above are only examples of positive electrode active materials, but are not limited thereto. Those skilled in the art can select a suitable positive electrode active material according to actual needs.

[0037] In a further embodiment of the present invention, the organic acid lithium is lithium maleate, and the content of lithium maleate is 0.23wt%-8.83wt%. Compared with other acids, maleic acid is more easily commercially available and more economical. By selecting the above content of lithium maleate, sufficient microporous structure and direct lithium ion channel can be generated in the positive electrode plate, and there is no waste, thereby saving costs.

[0038] According to another typical embodiment of the present invention, a method for preparing a positive electrode sheet is provided. The method comprises the following steps: - Step S1: mixing a positive electrode active material, a positive electrode conductive agent, a positive electrode binder and lithium carbonate to obtain a first slurry; - Step S2: adding an organic acid to the first slurry and mixing to obtain a second slurry, and then making the second slurry into a positive electrode sheet, or making the first slurry into a primary electrode sheet, and then applying an organic acid on the primary electrode sheet to make a positive electrode sheet.

[0039] In the method for preparing the positive electrode sheet of the present invention, lithium carbonate is mixed with the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder, so that lithium carbonate can occupy a position in the first slurry, and then an organic acid is added to the first slurry or applied to the primary electrode sheet, so that the organic acid reacts with lithium carbonate to generate CO2 and H2O, thereby generating more microporous structures and more direct lithium ion channels in the positive electrode sheet during the drying process, thereby reducing the tortuosity and McMullin number of the electrode sheet at the same body density, and improving the electrical properties of the battery such as conductivity and rate performance. At the same time, the addition of organic acid can effectively reduce the residual alkali content in the positive electrode active material and improve the processing performance of the slurry.

[0040] In a further embodiment, the method further comprises step S3: drying the positive electrode sheet obtained in step S2 to produce a positive electrode sheet with micropores. Through the drying step, CO2 and H2O generated in the neutralization reaction are volatilized better, which is more conducive to the generation of microporous structure and direct lithium ion channels.

[0041] Preferably, the drying temperature in step S3 may be 100-150° C. The drying temperature in step S3 may be 100° C., 105° C., 110° C., 115° C., 120° C., 125° C., 130° C., 135° C., 140° C., 145° C. or 150° C. Within the drying temperature range, CO2 and H2O generated in the neutralization reaction are better volatilized, thereby being more conducive to the generation of microporous structures and direct lithium ion channels.

[0042] In a further embodiment, the addition ratio of lithium carbonate is 0.05wt%-5wt% of the solid components in the first slurry. Within this addition ratio range, it can ensure that more microporous structures and more direct lithium ion channels are generated in the positive electrode sheet, and it can also better ensure that other performances of the battery will not be adversely affected.

[0043] The addition ratio of lithium carbonate can be 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.5wt%, 0.8wt%, 1wt%, 1.2wt%, 1.5wt%, 1.8wt%, 2wt%, 2.2wt%, 2.5wt%, 2.8wt%, 3wt%, 3.2wt%, 3.5wt%, 3.8wt%, 4wt%, 4.2wt%, 4.5wt%, 4.8wt% or 5wt% of the solid components in the first slurry.

[0044] In a further embodiment, the organic acid is selected from one or more of maleic acid, glycolic acid, acrylic acid, fumaric acid, malonic acid, succinic acid, malic acid, trisaccharic acid and aconitic acid. The organic acids from the above list are easily commercially available and more economical, and by using the organic acids from the above list, CO2 and H2O can be better produced in the neutralization reaction, thereby generating more microporous structures and more direct lithium ion channels in the positive electrode sheet during the drying process.

[0045] In a further embodiment, the positive electrode active material is selected from one or more of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, lithium titanate and lithium manganese iron phosphate. The above are only examples of positive electrode active materials, but are not limited thereto. Those skilled in the art can select a suitable positive electrode active material according to actual needs.

[0046] In a further embodiment, the particle size of lithium carbonate is 50 nm-10 μm. Within this particle size range, the size of the generated micropores can be effectively controlled by the reaction of lithium carbonate with an organic acid, thereby more advantageously improving the electrical properties of the battery, such as conductivity and rate performance.

[0047] The particle size of lithium carbonate can be 50nm, 1 micron, 1.1 micron, 1.2 micron, 1.3 micron, 1.4 micron, 1.5 micron, 1.6 micron, 1.7 micron, 1.8 micron, 1.9 micron, 2 micron, 2.1 micron, 2.2 micron, 2.3 micron, 2.4 micron, 2.5 micron, 2.6 micron, 2.7 micron, 2.8 micron, 2.9 micron, 3 micron, 3.1 micron, 3.2 micron, 3.3 micron, 3.4 micron, 3.5 micron, 3.6 micron, 3.7 micron, 3.8 micron, 3.9 micron, 4 micron, 4.1 micron, 4.2 micron, 4.3 micron, 4.4 micron, 4.5 micron, 4.6 micron, 4.7 micron, 4.8 micron, 4.9 micron, 5 micron, 5.1 micron, 5.2 micron, 5.3 micron, 5.4 micron, 5.5 micron, 5.6 micron, 5.7 micron, 5.8 micron, 5.9 micron, 6 micron, 6. 4 microns, 5.5 microns, 5.6 microns, 5.7 microns, 5.8 microns, 5.9 microns, 6 microns, 6.1 microns, 6.2 microns, 6.3 microns, 6.4 microns, 6.5 microns, 6.6 microns, 6.7 microns, 6.8 microns, 6.9 microns, 7 microns, 7.1 microns, 7.2 microns, 7.3 microns, 7.4 microns, 7.5 microns, 7.6 microns, 7.7 microns, 7.8 microns, 7.9 microns, 8 microns, 8.1 microns, 8.2 microns, 8.3 microns, 8.4 microns, 8.5 microns, 8.6 microns, 8.7 microns, 8.8 microns, 8.9 microns, 9 microns, 9.1 microns, 9.2 microns, 9.3 microns, 9.4 microns, 9.5 microns, 9.6 microns, 9.7 microns, 9.8 microns, 9.9 microns or 10 microns.

[0048] In a further embodiment, step S1 includes the following steps: -Step S11: Mix the positive electrode conductor, the positive electrode binder and the solvent to obtain a uniform solution; -Step S12: Add lithium carbonate to the uniform solution to obtain a conductive glue; -Step S13: Add the positive electrode active material to the conductive glue to obtain a first slurry.

[0049] In a further embodiment, step S2 includes the following steps: -Step S21: adding an organic acid to the first slurry and mixing to obtain a second slurry, and then evenly coating the second slurry on an aluminum foil to form a positive electrode sheet; or -Step S22: evenly coating the first slurry on an aluminum foil to form a primary electrode sheet, and then spraying an organic acid ethanol solution on the primary electrode sheet or soaking the primary electrode sheet with an organic acid ethanol solution to form a positive electrode sheet.

[0050] In a further embodiment, after step S22, step S2 further includes step S23: washing the positive electrode plate with an ethanol solution. Using ethanol to wash the positive electrode plate can wash away the residual organic acid on the positive electrode plate, thereby reducing the influence of the residual organic acid on the electrical properties of the plate after drying.

[0051] According to another typical embodiment of the present invention, a lithium-ion battery is provided, comprising: a positive electrode plate, a negative electrode plate and a separator, wherein the positive electrode plate is the positive electrode plate described above in the present invention or is prepared by the method described above in the present invention.

[0052] In the technical solution of the present invention, by adding lithium carbonate to the slurry and adding organic acid to the slurry or soaking the pole piece in organic acid, CO2 and H2O generated in the neutralization reaction are generated in the positive pole piece during the drying process, so that the tortuosity and McMullin number of the pole piece are reduced at the same body density, and the electrical properties of the battery such as conductivity and rate performance are improved. At the same time, the addition of organic acid can effectively reduce the residual alkali content in the positive active material and improve the processing performance of the slurry.

[0053] Example

[0054] Preparation of positive electrode

[0055] Example 1 (LFP-1)

[0056] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.5 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0057] 2) After the glue solution is evenly mixed, 92.5 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0058] 3) adding 0.93 g of maleic acid (consistent with the molar ratio of the total lithium carbonate in the slurry) to the first slurry and continuing stirring for half an hour to obtain a second slurry;

[0059] 4) The second slurry is evenly coated on the aluminum foil, and the surface density is controlled to be about 20 mg / cm 2 , bake at 100℃ for 10min to obtain the positive electrode sheet.

[0060] Example 2 (LFP-2)

[0061] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.8 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0062] 2) After the glue solution is evenly mixed, 92.2 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0063] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 22 mg / cm 2 , the primary electrode was dried in an oven at 100°C, then immersed in 300ml of 1wt% maleic acid ethanol solution, and baked at 100°C for 10min to obtain the positive electrode.

[0064] Example 3 (LFP-3)

[0065] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.8 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0066] 2) After the glue solution is evenly mixed, 92.2 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0067] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 22 mg / cm 2 , drying the primary electrode in an oven at 100° C., and then immersing it in 300 ml of 1 wt% maleic acid ethanol solution to obtain a positive electrode;

[0068] 4) After drying at 100° C., the positive electrode sheet was immersed in 300 ml of ethanol solution to clean the maleic acid solution remaining on the positive electrode sheet, and finally the positive electrode sheet was dried in an oven at 100° C.

[0069] Example 4 (LCO-4)

[0070] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 25 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.5 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0071] 2) After the glue solution is evenly mixed, 92.5 g of lithium cobalt oxide positive electrode active material is added, mixed thoroughly and diluted with 3.2 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0072] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 20 mg / cm 2 , the primary electrode was dried in an oven at 100°C, then immersed in 300ml of 1wt% maleic acid ethanol solution, and baked at 100°C for 10min to obtain the positive electrode.

[0073] Example 5 (LTO-5)

[0074] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 1 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution and stirred for 30 min to obtain a conductive glue solution;

[0075] 2) After the glue solution is evenly mixed, 92 g of lithium titanate positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0076] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 20 mg / cm 2 , the primary electrode was dried in an oven at 100°C, then immersed in 300ml of 1wt% maleic acid ethanol solution, and baked at 100°C for 10min to obtain the positive electrode.

[0077] Example 6 (LMFP-6)

[0078] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.2 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0079] 2) After the glue solution is evenly mixed, 92.8 g of lithium manganese iron phosphate positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity range to 5-10 Pa·s to obtain a first slurry;

[0080] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 20 mg / cm 2 , the primary electrode was dried in an oven at 100°C, then immersed in 300ml of 1wt% maleic acid ethanol solution, and baked at 100°C for 10min to obtain the positive electrode.

[0081] Example 7 (LMO-7)

[0082] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 25 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.5 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0083] 2) After the glue solution is evenly mixed, 92.5 g of lithium manganate positive electrode active material is added, mixed thoroughly and diluted with 4 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain a first slurry;

[0084] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be about 20 mg / cm 2 , the primary electrode was dried in an oven at 100°C, then immersed in 300ml of 1wt% maleic acid ethanol solution, and baked at 100°C for 10min to obtain the positive electrode.

[0085] Example 8 (LCO-8)

[0086] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 25 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.5 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0087] 2) After the glue solution is evenly mixed, 92.5 g of lithium cobalt oxide positive electrode active material is added, mixed thoroughly and diluted with 3.2 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0088] 3) adding 0.785 g of maleic acid (consistent with the molar ratio of the total lithium carbonate in the slurry) to the first slurry and continuing stirring for half an hour to obtain a second slurry;

[0089] 4) The second slurry is evenly coated on the aluminum foil, and the surface density is controlled to be about 20 mg / cm 2 , bake at 100℃ for 10min to obtain the positive electrode sheet.

[0090] Example 9 (LMFP-9)

[0091] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.2 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0092] 2) After the glue solution is evenly mixed, 92.8 g of lithium manganese iron phosphate positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity range to 5-10 Pa·s to obtain a first slurry;

[0093] 3) adding 0.31 g of maleic acid (consistent with the molar ratio of the total lithium carbonate in the slurry) to the slurry and continuing stirring for half an hour to obtain a second slurry;

[0094] 4) The second slurry is evenly coated on the aluminum foil, and the surface density is controlled to be about 20 mg / cm 2 , bake at 100℃ for 10min to obtain the positive electrode sheet.

[0095] Example 10 (LFP-10)

[0096] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.8 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0097] 2) After the glue solution is evenly mixed, add 92.2g of lithium iron phosphate positive electrode active material (containing 0.1% lithium carbonate), mix thoroughly and dilute with 12ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10Pa·s;

[0098] 3) Apply the slurry evenly on the aluminum foil, and control the surface density to 22mg / cm 2 , dry the primary electrode in an oven at 100°C, and soak it in 300ml of 1% glycolic acid ethanol solution, and bake it at 100°C for 10min to obtain the positive electrode.

[0099] Example 11 (LFP-11)

[0100] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.8 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0101] 2) After the glue solution is evenly mixed, 92.2 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0102] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 22 mg / cm 2 , dry the primary electrode in an oven at 100°C, then soak it in 300ml of 1wt% acrylic acid ethanol solution, and bake it at 100°C for 10min to obtain the positive electrode.

[0103] Example 12 (LFP-12)

[0104] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.8 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0105] 2) After the glue solution is evenly mixed, 92.2 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0106] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 22 mg / cm 2 , the primary electrode was dried in an oven at 100°C, then immersed in 300ml of 1wt% fumaric acid ethanol solution, and baked at 100°C for 10min to obtain the positive electrode.

[0107] Example 13 (LFP-13)

[0108] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.8 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0109] 2) After the glue solution is evenly mixed, 92.2 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0110] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 22 mg / cm 2 , dry the primary electrode in an oven at 100°C, then soak it in 300ml of 1wt% malonic acid ethanol solution, and bake it at 100°C for 10min to obtain the positive electrode.

[0111] Example 14 (LFP-14)

[0112] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.8 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0113] 2) After the glue solution is evenly mixed, 92.2 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0114] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 22 mg / cm 2 , the primary electrode was dried in an oven at 100°C, and at the same time, immersed in 300 ml of 1 wt% succinic acid ethanol solution, and baked at 100°C for 10 min to obtain a positive electrode.

[0115] Example 15 (LFP-15)

[0116] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.8 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0117] 2) After the glue solution is evenly mixed, 92.2 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0118] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 22 mg / cm2 , the primary electrode was dried in an oven at 100°C, then immersed in 300ml of 1wt% malic acid ethanol solution, and baked at 100°C for 10min to obtain the positive electrode.

[0119] Example 16 (LFP-16)

[0120] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.8 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0121] 2) After the glue solution is evenly mixed, 92.2 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0122] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 22 mg / cm 2 , the primary electrode was dried in an oven at 100°C, and at the same time, immersed in 300 ml of 1 wt% triacyl ethanol solution, and baked at 100°C for 10 min to obtain a positive electrode.

[0123] Example 17 (LFP-17)

[0124] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.8 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0125] 2) After the glue solution is evenly mixed, 92.2 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0126] 3) The first slurry is evenly coated on the aluminum foil to obtain the primary electrode, and the surface density is controlled to be 22 mg / cm 2 , the primary electrode was dried in an oven at 100°C, then immersed in 300ml of 1wt% aconitic acid ethanol solution, and baked at 100°C for 10min to obtain the positive electrode.

[0127] Example 18 (LFP-18)

[0128] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.05 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0129] 2) After the glue solution is evenly mixed, 92.95 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain a first slurry;

[0130] 3) adding 0.225 g of maleic acid to the first slurry and continuing stirring for half an hour to obtain a second slurry;

[0131] 4) The second slurry is evenly coated on the aluminum foil, and the surface density is controlled to be about 20 mg / cm 2 , bake at 100℃ for 10min to obtain the positive electrode sheet.

[0132] Example 19 (LFP-19)

[0133] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 5 g of lithium carbonate (particle size of about 3 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0134] 2) After the glue solution is evenly mixed, 88g of lithium iron phosphate (containing 0.1wt% lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10Pa·s to obtain the first slurry;

[0135] 3) adding 7.99 g of maleic acid to the first slurry and continuing stirring for half an hour to obtain a second slurry;

[0136] 4) The second slurry is evenly coated on the aluminum foil, and the surface density is controlled to be about 20 mg / cm 2 , bake at 100℃ for 10min to obtain the positive electrode sheet.

[0137] Example 20 (LFP-20)

[0138] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.5 g of lithium carbonate (particle size of about 50 nm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0139] 2) After the glue solution is evenly mixed, 92.5 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain the first slurry;

[0140] 3) adding 0.93 g of maleic acid to the first slurry and continuing stirring for half an hour to obtain a second slurry;

[0141] 4) The second slurry is evenly coated on the aluminum foil, and the surface density is controlled to be about 20 mg / cm 2 , bake at 100℃ for 10min to obtain the positive electrode sheet.

[0142] Example 21 (LFP-21)

[0143] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution, and then 0.5 g of lithium carbonate (particle size of about 10 μm) was added to the uniform solution, and stirring was continued for 30 min to obtain a conductive glue solution;

[0144] 2) After the glue solution is evenly mixed, 92.5 g of lithium iron phosphate (containing 0.1 wt% lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain a first slurry;

[0145] 3) adding 0.93 g of maleic acid to the first slurry and continuing stirring for half an hour to obtain a second slurry;

[0146] 4) The second slurry is evenly coated on the aluminum foil, and the surface density is controlled to be about 20 mg / cm 2 , bake at 100℃ for 10min to obtain the positive electrode sheet.

[0147] Control group 1 (LFP-1s)

[0148] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution;

[0149] 2) After the solution is mixed evenly, 93 g of lithium iron phosphate (containing 0.1 wt % of lithium carbonate) positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain a slurry;

[0150] 3) Apply the slurry evenly on the aluminum foil, and control the surface density to about 20mg / cm 2 , bake at 100℃ for 10min to obtain the positive electrode sheet.

[0151] Control group 2 (LCO-2s)

[0152] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 25 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution;

[0153] 2) After the solution is mixed evenly, 93 g of lithium cobalt oxide positive electrode active material is added, mixed thoroughly and diluted with 3.2 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain a slurry;

[0154] 3) Apply the slurry evenly on the aluminum foil, and control the surface density to about 20mg / cm 2 , and baked in an oven at 100°C for 10 min to obtain the positive electrode sheet.

[0155] Control group 3 (LTO-3s)

[0156] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution;

[0157] 2) After the solution is mixed evenly, 93 g of lithium titanate material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain a slurry;

[0158] 3) Apply the slurry evenly on the aluminum foil, and control the surface density to about 20mg / cm 2 , and baked in an oven at 100°C for 10 min to obtain the positive electrode sheet.

[0159] Control group 4 (LMFP-4s)

[0160] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution;

[0161] 2) After the solution is mixed evenly, 93 g of lithium manganese iron phosphate positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain a slurry;

[0162] 3) Apply the slurry evenly on the aluminum foil, and control the surface density to about 20mg / cm 2 , and baked in an oven at 100°C for 10 min to obtain the positive electrode sheet.

[0163] Control group 5 (LMO-5s)

[0164] 1) 3 g of carbon black positive electrode conductive agent, 4 g of PVDF positive electrode binder and 42 ml of N-methylpyrrolidone solvent were mixed and placed in a planetary mixer to mix into a uniform solution;

[0165] 2) After the solution is mixed evenly, 93 g of lithium manganate positive electrode active material is added, mixed thoroughly and diluted with 12 ml of N-methylpyrrolidone solvent to control the viscosity in the range of 5-10 Pa·s to obtain a slurry;

[0166] 3) Apply the slurry evenly on the aluminum foil, and control the surface density to about 20mg / cm 2 , and baked in an oven at 100°C for 10 min to obtain the positive electrode sheet.

[0167] Preparation of electrolyte

[0168] 10 g of ethylene carbonate, 30 g of dimethyl carbonate, and 10 g of lithium hexafluorophosphate were mixed to prepare an electrolyte solution.

[0169] Battery Assembly

[0170] Assemble CR2016 button half-cells in a dry laboratory. Use the positive electrode sheet obtained in the above steps as the positive electrode and the lithium sheet as the negative electrode. Assemble the positive electrode, negative electrode, separator and button battery shell and inject electrolyte. After the battery is assembled, let it stand for about 24 hours to age, thereby obtaining a button half-cell.

[0171] Battery performance test

[0172] 1. Determination of McMullin number (Nm)

[0173] Two pole pieces (diameters of 15 mm and 17 mm, respectively) were pressed as the positive electrode and the negative electrode, respectively, and assembled with a glass fiber separator (diameter of 20 mm) into a single-layer soft-pack battery. A lithium-free electrolyte (TBAClO4, Sigma Aldrich, ≥99.0%) was injected. The impedance in the range of 0.03-105 Hz was measured using an electrochemical workstation. According to the fitting method in the reference [Journal of The Electrochemical Society, 163 (7) A1373-A1387 (2016)], the impedance was obtained. Figure 3 The fitting curve is used to further calculate the ionic resistance R in the electrode sheet. Ion. The area A of the pole piece can be calculated based on the diameter of the pole piece 15mm, the thickness d of the pole piece (excluding the current collector) can be obtained through thickness testing, and the conductivity κ of the electrolyte can be obtained through conductivity testing. Substituting the obtained data into the following formula, the Nm value of the pole piece can be obtained. The pole piece porosity ε can be calculated by the density of each component in the pole piece and the volume of the pole piece. According to the following formula, when the Nm value and ε are known, the curvature τ can be calculated.

[0174]

[0175] 2. Determination of rate retention

[0176] Use a charge and discharge instrument to test the rate performance of the battery. First, charge at an ambient temperature of 23°C, a charging voltage of 3.7V, and a charging current of 1C, and then discharge at a discharge current of 0.2C and a cut-off voltage of 2.5V (discharge capacity at a rate of 0.2C). Next, charge at an ambient temperature of 23°C, a charging voltage of 3.7V, and a charging current of 1C, and discharge at a discharge current of 10C and a cut-off voltage of 2.5V (discharge capacity at a rate of 10C). Calculate the ratio of the discharge capacity at a rate of 0.2C to the discharge capacity at a rate of 10C, which is the rate retention rate (%).

[0177] Rate retention ratio [%] = (discharge capacity at 0.2C rate / discharge capacity at 10C rate) × 100%.

[0178] 3. Determination of capacity retention rate

[0179] The discharge capacity and cycle performance of the battery are tested using a charge and discharge instrument.

[0180] First, charge at an ambient temperature of 23°C, a charging voltage of 3.7V, and a charging current of 0.2C, and then discharge at a discharge current of 0.2C and a cut-off voltage of 2.5V, and measure the first discharge capacity (discharge capacity of the 1st cycle). Next, charge and discharge are repeated at an ambient temperature of 23°C, a charging voltage of 3.7V, a charging current of 1C, and at a discharge current of 2C and a cut-off voltage of 2.5V. Subsequently, the discharge capacity of the 100th cycle is measured. Next, based on the following formula, the capacity retention rate (%) after 100 cycles is calculated using the discharge capacity of the 1st cycle and the discharge capacity of the 100th cycle.

[0181] Capacity retention rate after 100 cycles [%] = (discharge capacity at the 100th cycle / discharge capacity at the 1st cycle) × 100%.

[0182] Table 1 shows the evaluation results of the batteries prepared according to Control Groups 1-5 and Examples 1-21.

[0183] Table 1

[0184]

[0185]

[0186] From the comparison of the control group 1 (LFP-1s) and examples 1 (LFP-1) to 21 (LFP-21) in Table 1, it can be seen that when lithium iron phosphate (LFP) is used as the positive electrode active material, the addition of organic acid and lithium carbonate significantly reduces the Nm of the positive electrode sheet and improves the capacity retention rate and rate performance of the battery.

[0187] From the comparison of control group 2 (LCO-2s) with embodiment 4 (LCO-4) and embodiment 8 (LCO-8) in Table 1, it can be seen that when lithium cobalt oxide (LCO) is used as the positive electrode active material, the addition of organic acid and lithium carbonate also significantly reduces the Nm of the positive electrode sheet and improves the capacity retention rate and rate performance of the battery.

[0188] From the comparison between the control group 3 (LTO-3s) and the embodiment 5 (LTO-5) in Table 1, it can be seen that when lithium titanate (LTO) is used as the positive electrode active material, the addition of organic acid and lithium carbonate also significantly reduces the Nm of the positive electrode sheet and improves the capacity retention rate and rate performance of the battery.

[0189] From the comparison of the control group 4 (LMFP-4s) with the embodiment 6 (LMFP-6) and the embodiment 9 (LMFP-9) in Table 1, it can be seen that when lithium manganese iron phosphate (LMFP) is used as the positive electrode active material, the addition of organic acid and lithium carbonate also significantly reduces the Nm of the positive electrode sheet and improves the capacity retention rate and rate performance of the battery.

[0190] Moreover, from the comparison between the control group 5 (LMO-5s) and the embodiment 7 (LMO-7) in Table 1, it can be seen that when lithium manganese oxide (LMO) is used as the positive electrode active material, the addition of organic acid and lithium carbonate also significantly reduces the Nm of the positive electrode sheet and improves the capacity retention rate and rate performance of the battery.

[0191] In addition, from Figure 1 It can be seen that by adding lithium carbonate and organic acid to the slurry and neutralizing the CO2 and H2O produced in the reaction, a microporous structure and more direct lithium ion channels are generated in the electrode during the drying process, thereby reducing the tortuosity of the electrode at the same body density.

[0192] It can be seen from the above experimental results that the above embodiments of the present invention achieve the following technical effects:

[0193] By adding lithium carbonate to the slurry and adding organic acid to the slurry or soaking the pole piece in organic acid, CO2 and H2O generated in the neutralization reaction are generated in the pole piece during the drying process, so that the tortuosity and McMullin number (Nm) of the pole piece are reduced at the same body density, and the electrical properties of the battery such as conductivity and rate performance are improved. At the same time, the addition of organic acid can effectively reduce the residual alkali content in the positive electrode active material and improve the processing performance of the slurry.

[0194] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: The invention comprises a positive electrode active material, a positive electrode conductor, a positive electrode binder and an organic acid lithium, wherein the content of the organic acid lithium is 0.14wt%-11.99wt% based on the total weight of the positive electrode active material, the positive electrode conductor, the positive electrode binder and the organic acid lithium.

2. The positive electrode sheet according to claim 1, characterized in that: The positive electrode plate contains micropores of 1-10 microns, and the organic acid lithium is enriched around the micropores.

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The organic acid lithium is distributed on the surfaces of the positive electrode active material and the positive electrode conductive agent.

4. The positive electrode sheet according to claim 1 or 2, characterized in that: The organic acid radical in the organic acid lithium is derived from one or more of maleic acid, glycolic acid, acrylic acid, fumaric acid, malonic acid, succinic acid, malic acid, trisaccharic acid and aconitic acid.

5. The positive electrode sheet according to claim 1 or 2, characterized in that: The positive electrode active material is selected from one or more of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, lithium titanate and lithium iron manganese phosphate.

6. The positive electrode sheet according to claim 1 or 2, characterized in that: The organic acid lithium is lithium maleate, and the content of lithium maleate is 0.23wt%-8.83wt%.

7. A method for preparing a positive electrode sheet, characterized in that: The following steps are involved: - Step S1: mixing a positive electrode active material, a positive electrode conductive agent, a positive electrode binder and lithium carbonate to obtain a first slurry; - Step S2: adding an organic acid to the first slurry and mixing to obtain a second slurry, and then making the second slurry into a positive electrode sheet, or making the first slurry into a primary electrode sheet, and then applying an organic acid on the primary electrode sheet to make a positive electrode sheet.

8. The method according to claim 7, characterized in that The method further comprises step S3: drying the positive electrode sheet obtained in step S2 to prepare a positive electrode sheet with micropores. Preferably, the drying temperature in step S3 is 100-150°C.

9. The method according to claim 7 or 8, characterized in that: The addition ratio of the lithium carbonate is 0.05wt%-5wt% of the solid components in the first slurry.

10. The method according to claim 7 or 8, characterized in that: The organic acid is selected from one or more of maleic acid, glycolic acid, acrylic acid, fumaric acid, malonic acid, succinic acid, malic acid, triglyceric acid and aconitic acid.

11. The method according to claim 7 or 8, characterized in that: The positive electrode active material is selected from one or more of lithium manganese oxide, lithium cobalt oxide, lithium iron phosphate, lithium titanate and lithium iron manganese phosphate.

12. The method according to claim 7 or 8, characterized in that: The particle size of the lithium carbonate is 50nm-10μm.

13. The method according to claim 7 or 8, characterized in that: The step S1 comprises the following steps: - Step S11: mixing the positive electrode conductive agent, the positive electrode binder and the solvent to obtain a uniform solution; - Step S12: adding lithium carbonate to the uniform solution to obtain a conductive glue solution; - Step S13: adding the positive electrode active material to the conductive adhesive to obtain the first slurry.

14. The method according to claim 7 or 8, characterized in that The step S2 comprises the following steps: - Step S21: adding an organic acid to the first slurry and mixing them to obtain a second slurry, and then uniformly coating the second slurry on an aluminum foil to prepare a positive electrode sheet; or - Step S22: uniformly coating the first slurry on an aluminum foil to form a primary electrode sheet, and then spraying an organic acid ethanol solution on the primary electrode sheet or soaking the primary electrode sheet in an organic acid ethanol solution to form a positive electrode sheet.

15. The method according to claim 14, characterized in that After step S22, step S2 further includes step S23: cleaning the positive electrode plate with an ethanol solution.

16. A lithium ion battery comprising: Positive electrode, The negative electrode, and Diaphragm, It is characterized in that The positive electrode plate is the positive electrode plate according to any one of claims 1 to 6 or is prepared by the method according to any one of claims 7 to 15.